On the Phase Diagram of Calcium Carbonate Solutions. Issue 1 (3rd June 2016) - Zou, Zhaoyong; Habraken, Wouter J. E. M.; Bertinetti, Luca; Politi, Yael; Gal, Assaf; Weiner, Stephen; Addadi, Lia; Fratzl, Peter
Abstract : A liquid–liquid phase boundary is experimentally determined in calcium carbonate solutions obtained by rapid mixing. Nanoparticles of amorphous calcium carbonate form at concentration higher than this boundary and their size diverges close to the boundary, which is interpreted as a spinodal line. At lower concentrations, the solution is metastable against the nucleation of crystalline calcium carbonate phases.